In-vitro silanization of dental enamel to prevent demineralization = Silanización in vitro sobre esmalte dental para prevenir desmineralización - Gutiérrez Camacho, José R.; Aguilera Galviz, Luis Alejandro; Sánchez Balderas, Gregorio; Palestino, Gabriela; Zavala Alonso, Norma Verónica (2022)
Caries is a multifactorial disease that can negatively affect dental tissues through the demineralization process, which produces acids deriving from the metabolism of carbohydrates. Some strategies to prevent this process have been proposed, such as topical fluoride application, resin-based restorations, pit and fissures sealers, infiltrated resins, vaccines, mouthwashes, and several brushing techniques. To evaluate in vitro enamel hydrophobic modification as a method of prevention against demineralization. A descriptive and comparative study was carried out. Thirty premolars extracted for orthodontic reasons were obtained, encapsulated in epoxy resin, sectioned, and sanded to obtain specimens 3mm in thickness. The samples were pretreated with NaOCl and EDTA, incubated with 1 and 4% octadeyltrichlorosilane (OTS) or with 3 and 6% octadecyltriethoxysilane (TEOS) for 5min and for 8h. Subsequently, the samples were immersed in citric acid for 2 months. The samples were analyzed by their contact angle, infrared spectroscopy, scanning electron microscopy, atomic and confocal force, before and after treatment in citric acid. The samples coated with 1 and 4% OTS for 5min and 8h kept the silanizing agent on their surface after 2 months in citric acid. The treatment with TEOS was only effective at 6% with a reaction time of 5min. The modification with 1 and 4% OTS protects the surface of the tooth enamel from demineralization in acidic medium. The results indicate that treatment with 4% OTS is effective from 5min, which makes it appropriate in clinical practice.
Caries es una enfermedad multifactorial que destruye en tejido dental por la desmineralización de ácidos generados en el metabolismo de carbohidratos. Algunos métodos preventivos, como fluoruro, resinas, selladores de fosetas y fisuras, resinas infiltradas, vacunas, enjuagues bucales, y un sinfín de técnicas de cepillado, han sido empleadas. Evaluar in vitro la modificación hidrofoba del esmalte como método preventivo en contra de la desmineralización. Un estudio decriptivo y comparativo fue empleado. Se obtuvieron treinta premolares sanos extraidos por razones ortodónticas y encapsulados en resina epóxica, seccionados y pulidos hasta obtener especímenes de 3mm de grosor. Las muestras fueron pretratadas con NaOCl y EDTA, incubadas en octadeciltriclosorilano (OTS) al 1 y 4% y octadeciltrietoxisilano (TEOS) 3 y 6% por 5min y 8h. Después, las muestras fueron sumergidas en ácido cítrico por 2 meses. Las muestras fueron analizadas con ángulo de contacto, espectroscopía infrarroja, microscopía electrónica de barrido, atómica y confocal, antes y después de tratamiento con ácido cítrico. Las muestras cubiertas con OTS 1 y 4% por 5min y 8h mantuvieron el agente silanizante sobre la superficie después de 2 meses en ácido cítrico. El tratamiento con TEOS fue efectivo al 6% y con un tiempo de reacción de 5min. La modificación con 1 y 4% de OTS proteje la superficie del esmalte dental contra la desmineralización en un medio ácido. Estos resultados indican que el tratamiento con OTS 4% es efectivo desde 5min de aplicación, lo cual es apropiado en la práctica clínica.
En revista Odóvtos, vol. 24, no.1 (enero-abril 2022)
Descripción basada en el contenido visto el 15 de noviembre, 2024
También disponible en formato HTML y EPUB